Designing a Framework of Stakeholders' Participation in School Sport Decisions - Akbar Mirzaei Kalar; Mehrali Hemmatinezhad; Rahim Ramazaninezhad (The Society of Aging and Physical Activity (SAPA), 2019)
Background. Stakeholders in school sport are individuals and groups whose role is to promote the success of sport programs, activities and events in schools. Understanding stakeholders' interests and behaviors can play a constructive role in the performance of schools. In this regard, their participation in the process of planning, implementing, and monitoring school sports is the best way to develop school sports. Objectives. The aim of this study was to identify and classify stakeholders to provide a framework for stakeholders' participation in school sport decisions. Methods. The present study employed a descriptive-survey research method. The research population consisted of all experts of the physical education department and health of education ministry, general offices of provinces, cities and towns, as well as physical education teachers. The data were collected in two steps: first the systematic interviewing technique was conducted with 16 specialists in the field of school sport to identify the stakeholders. Then, a researcher-made questionnaire in line with Freeman's Classification method (2007) and Mitchell's et al. stakeholder salience model with confirmed reliability and validity was distributed among the samples for stakeholders' categorization. Results. The results of the study suggested that students, teachers, and physical education and health department are the most important and primary stakeholders, followed by parents and governmental organizations. Conclusion. The results of the study revealed that the effective relationship between primary and secondary stakeholders and their participation in decision-making are the most significant factors for the proper performance of schools' sport.